Epileptic Seizure Classification using Deep Batch Normalization Neural Network - Purnomo, Adenuar; Tjandrasa, Handayani (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2020)
Epilepsy is a chronic noncommunicable brain disease. Manual inspection of long-term Electroencephalogram (EEG) records for detecting epileptic seizures or other diseases that lasted several days or weeks is a time-consuming task. Therefore, this research proposes a novel epileptic seizure classification architecture called the Deep Batch Normalization Neural Network (Deep BN 3 ), a BN 3 architecture with a deeper layer to classify big epileptic seizure data accurately. The raw EEG signals are first to cut into pieces and passed through the bandpass filter. The dataset is very imbalanced, so an undersampling technique was used to produce a balanced sample of data for the training and testing dataset. Furthermore, the balanced data is used to train the Deep BN 3 architecture. The resulting model classifies the EEG signal as an epileptic seizure or non-seizure. The classification of epileptic seizures using Deep BN 3 obtained pretty good results compared to other architectures used in this research, with an accuracy of 53.61%.